Evolution of infectious disease ward design in Malaysia : Case study - Mohd Nawawi, Norwina; Khoo, Boon Teck; Sapian, Abdul Razak; Sanusi, Aliyah Nur Zafirah; Md Alwi, Nadiah (2017)
Infectious disease is prevalent in all countries. Malaysia is no different. With the ease of global travel and incidental migration, all countries faced the phenomenon of infectious disease in various degree. proactive in its preparation to manage its emergence is the key of Malaysia's disease surveillance. This presentation focuses on the evolution of infectious disease ward design through the ages by case studies. through a historical review of old hospitals and the dos and don’t’s in the sample evaluation of selected infectious disease ward of the current design, findings found the odds in mitigating these infections (including hospital acquired infection (HAI) are just too many and unknown. To date, isolation rooms at each ward discipline are utilised as barrier nursing – to isolate from infection or causing infection in all hospitals. only selected hospitals, due to budget and geography of its occurrence, purposed built wards for infectious disease, were eventually built. In the convergence of the disease in one centre, health status of the staff matters. Innovating balance needs for staff, patient and the extended caregivers (relative), a mixed approach catering all users, were formulated. either as new and as a retrofit, on land or at higher levels, will depend on its physical requirements and placement locality. although outcome is yet to be evaluated the final design is akin to historical moves i.e isolated, landed, ease of access.